2023
DOI: 10.3390/f14040736
|View full text |Cite
|
Sign up to set email alerts
|

Potential Westward Spread of Emerald Ash Borer, Agrilus planipennis Fairmaire, 1888 (Coleoptera: Buprestidae) from Eastern Ukraine

Abstract: Emerald ash borer (EAB), Agrilus planipennis, is a phloem-boring beetle, native to East Asia that has become a serious invasive pest of ash (Fraxinus spp.) trees in North America and European Russia since the early 2000s. In 2019, EAB was detected in Ukraine. It had spread over 300 km from the entry point over two years and killed hundreds of Fraxinus excelsior and F. pennsylvanica trees. EAB poses a threat to the ash forests of neighboring European countries, which have already been damaged by the invasive fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…It has been demonstrated that EAB is well-adapted to temperature variations [6]. Particularly in Ukraine, using the MaxEnt model and 19 bioclimatic variables [9] resulted in high accuracy (AUC = 0.988) in predicting EAB invasion for 87% (Luhansk), 48% (Kharkiv), and 32% (Donetsk). Field inspection confirmed that EAB spread in 2020-2021 in most of the Luhansk region and the southeast of the Kharkiv region [14].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been demonstrated that EAB is well-adapted to temperature variations [6]. Particularly in Ukraine, using the MaxEnt model and 19 bioclimatic variables [9] resulted in high accuracy (AUC = 0.988) in predicting EAB invasion for 87% (Luhansk), 48% (Kharkiv), and 32% (Donetsk). Field inspection confirmed that EAB spread in 2020-2021 in most of the Luhansk region and the southeast of the Kharkiv region [14].…”
Section: Discussionmentioning
confidence: 99%
“…Within two years, the EAB has expanded its reach over 300 km westward from the initial detection site, colonizing hundreds of trees, both F. excelsior and F. pennsylvanica [9]. By the end of 2021, the pest was detected in most of the Luhansk region and the neighboring part of the Kharkiv region [9]. In 2022, EAB was identified in the parks of Kyiv [10], and by 2023, it had spread to a significant part of the Kharkiv region [11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations